2022
DOI: 10.1073/pnas.2202653119
|View full text |Cite
|
Sign up to set email alerts
|

A ribavirin-induced ORF2 single-nucleotide variant produces defective hepatitis E virus particles with immune decoy function

Abstract: Hepatitis E virus (HEV) is the causative agent of hepatitis E in humans and is the leading cause of enterically transmitted viral hepatitis worldwide. Ribavirin (RBV) is currently the only treatment option for many patients; however, cases of treatment failures or posttreatment relapses have been frequently reported. RBV therapy was shown to be associated with an increase in HEV genome heterogeneity and the emergence of distinct HEV variants. In this study, we analyzed the impact of eight patient-derived open … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 71 publications
0
7
0
Order By: Relevance
“…A major advantage of rabbit HEV-3ra over human HEV-3 is that the mutations in HEV-3ra can be readily tested with a homologous animal model since HEV-3ra naturally infects rabbits and causes persistent infection. Nevertheless, it should be noted that the rabbit HEV-3ra LR grows less efficiently in cultured cells than human HEV-3 Kernow-C1/p6 ( 21 , 22 , 50 , 60 62 ).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…A major advantage of rabbit HEV-3ra over human HEV-3 is that the mutations in HEV-3ra can be readily tested with a homologous animal model since HEV-3ra naturally infects rabbits and causes persistent infection. Nevertheless, it should be noted that the rabbit HEV-3ra LR grows less efficiently in cultured cells than human HEV-3 Kernow-C1/p6 ( 21 , 22 , 50 , 60 62 ).…”
Section: Discussionmentioning
confidence: 95%
“…Of note, the Y1320H/K1383N/G1634R/triple mutant is associated with RBV resistance in a clinical case, and in vitro studies showed that Y1320H and G1634R enhance HEV replication, whereas K1383N decreases HEV replication but increases RBV susceptibility, thereby contradicting the clinical observation ( 21 ). More recently, additional amino acid substitutions (P25S, G38S, A64T, G71R, P79S, S95P, V245I, and T324S) in HEV-3 ORF2 protein are reportedly associated with a sustained viral response despite RBV therapy, and the P79S mutant impaired antibody-mediated neutralization of HEV-3, thus potentially acting as an immune decoy ( 20 , 22 ). Nonetheless, due to the lack of a tractable and relevant animal model for chronic HEV-3 infection, the mechanisms of action or clinical relevance of these RBV treatment failure-associated mutations in HEV-3 replication and pathogenesis are largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, participation of the ORF2 and ORF3 proteins in RNA replication cannot be evaluated. The recent description of an ORF2 single nucleotide variant which may affect viral RNA replication [57] is supporting this concern. Hence, results obtained in a subgenomic replicon system should be validated in a full-length HEV RNA replication and/or infection system.…”
Section: Subgenomic Replicons As Tools To Study Hev Rna Replicationmentioning
confidence: 92%
“…The number of FFU were counted using the analyzing software of the Immunospot analyzer or FIJI in combination with CellProfiler [85, 86]. For visualization of full 96-well fluorescence images a maximum filter (r=10 pixels) was applied as previously described [87].…”
Section: Methodsmentioning
confidence: 99%